2001
DOI: 10.1161/hc2501.092492
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Tissue Factor Pathway Inhibitor Promotes Atherosclerosis and Thrombosis in Mice

Abstract: Background-Tissue factor initiates blood coagulation after atherosclerotic plaque disruption. Tissue factor pathway inhibitor (TFPI) inhibits tissue factor activity and may reduce thrombus formation in this setting. We evaluated the effect of heterozygous TFPI deficiency on the development of atherosclerosis and thrombosis in atherosclerosis-prone mice. Methods and Results-Mice with a combined heterozygous TFPI deficiency and homozygous apolipoprotein E deficiency (TFPI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 23 publications
6
123
2
Order By: Relevance
“…Previous studies have demonstrated that loss of TFPI promotes vascular thrombosis,33 thus the elevated expression of TFPI and PTGIS in the apex may inhibit thrombosis at a location at which OSI is elevated, WSS is low, and blood residence time is significantly increased. These data contrast with reports of arterial EC experiments in vitro that showed no effect of oscillatory flow on TFPI gene expression 34, 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that loss of TFPI promotes vascular thrombosis,33 thus the elevated expression of TFPI and PTGIS in the apex may inhibit thrombosis at a location at which OSI is elevated, WSS is low, and blood residence time is significantly increased. These data contrast with reports of arterial EC experiments in vitro that showed no effect of oscillatory flow on TFPI gene expression 34, 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…We previously have demonstrated that heterozygous Tfpi deficiency in mice affected time to occlusive thrombosis after endothelial injury at the site of an atherosclerotic plaque. 11 However, no difference in the time to occlusion was noted in the absence of preexisting vascular disease. In the present study, we have demonstrated that heterozygous Tfpi deficiency is uniformly lethal in mice that are also homozygous for FvL, whereas neither defect alone results in significant mortality.…”
Section: Mating Pairsmentioning
confidence: 96%
“…15 Tissue fibrin(ogen) staining was graded by a blinded observer using a qualitative scale roughly corresponding to the amount of stainable fibrin(ogen) as a percentage of each section (0, 0%; 1, 1% to 10%; 2, 11% to 50%; and 3, 51% to 100%). Adult mice were perfusion fixed as previously described, 11 and multiple organs were sectioned and stained with H&E.…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…The surface area occupied by atherosclerosis was then quantitated at the thoracic aorta and major branches, including the brachiocephalic, carotid, and subclavian arteries, via Oil Red O staining and quantitative morphometry, as described previously. 15 The lesion area was calculated for the control and treatment groups and expressed as a percentage of total surface area examined (nϭ10 per group). Additional analysis of lesion thickness was performed on hematoxylin and eosin-stained cross-sections obtained from the ascending aorta and brachiocephalic and carotid arteries.…”
Section: Analysis Of Atherosclerosismentioning
confidence: 99%